Increased serum CA 19-9 antibodies in Sjögren's syndrome. Issue 875 (September 1998) - Safadi, R.; Ligumsky, M.; Goldin, E.; Ilan, Y.; Haviv, Y. S.; Nusair, S.
Abstract : A 67-year-old woman with a history of thyroiditis presented with recent intermittent epigastric pain and nausea. Hyperamylasaemia, oedema of the pancreas, and high serum levels of lipase and CA 19-9 were found. Xerostomia and dry eyes developed later, accompanied by an abnormal Schirmer's test. The diagnosis of Sjögren's syndrome was confirmed by increased anti-Ro and anti-La antibodies and the histological findings of parotid gland biopsy. Two additional cases of Sjögren's syndrome with elevated serum CA 19-9 are also described. These observations of elevated serum lipase and serum CA 19-9 in Sjögren's syndrome without evidence of malignancy may reflect pancreatic involvement in this disorder.